The Importance of Compost in the Present Food Self-Sufficiency Drive and a few Methods of Preparing It - Mathauda, G. S. (Indian Forester, 1949)
We should improve our agricultural practices in order to make up the present deficiency in food grains. The importance of better manurial practices is self evident. Out of the 3 types of manures viz., farm-yard manure, inorganic or artificial manures and compost, only the last can be produced immediately in sufficiently large quantities and at a very 1ow cost. Also, it is decidedly superior to the artificial manures and, if properly made, better than the farm-yard manure too. A few simple methods of compost making are described.